2023
DOI: 10.1002/fsn3.3511
|View full text |Cite
|
Sign up to set email alerts
|

Research on irradiated food status and consumer acceptance: A Chinese perspective

Abstract: China is currently the world's largest producer of food irradiation. Despite the long‐standing (about 100 years) evidence supporting the safety of food irradiation, consumers’ acceptance of irradiated foods remains limited. This study aimed to investigate the development of food irradiation in China and identify the barriers that keep consumers away from irradiated foods. This was accomplished by exploring the relevant policies of food irradiation, the size and distribution of irradiation facilities in China, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Under the guidelines developed by the Codex Alimentarius Commission, gamma ray irradiation of food at doses up to 10 kGy is considered safe for human consumption [34]. Regulations in the US and China permit the irradiation of frozen food up to 7 kGy and 8 kGy, respectively [35,36]. For our study, we used the dose of 6 kGy of gamma irradiation, as previous studies have shown that this level of irradiation can reduce pathogen levels in meat samples by more than six orders of magnitude [37][38][39].…”
Section: Inoculation Of Chicken Meat Samplesmentioning
confidence: 99%
“…Under the guidelines developed by the Codex Alimentarius Commission, gamma ray irradiation of food at doses up to 10 kGy is considered safe for human consumption [34]. Regulations in the US and China permit the irradiation of frozen food up to 7 kGy and 8 kGy, respectively [35,36]. For our study, we used the dose of 6 kGy of gamma irradiation, as previous studies have shown that this level of irradiation can reduce pathogen levels in meat samples by more than six orders of magnitude [37][38][39].…”
Section: Inoculation Of Chicken Meat Samplesmentioning
confidence: 99%